Copy‐number variation of MCL1 predicts overall survival of non‐small‐cell lung cancer in a Southern Chinese population. (5th June 2016) - Yin, Jieyun; Li, Yangkai; Zhao, Hao; Qin, Qin; Li, Xiaorong; Huang, Jiao; Shi, Yun; Gong, Shufang; Liu, Li; Fu, Xiangning; Nie, Shaofa; Wei, Sheng
Abstract: BCL2L1 and MCL1 are key anti‐apoptotic genes, and critical for cancer progression. The prognostic values of BCL2L1 and MCL1 copy‐number variations (CNVs) in non‐small‐cell lung cancer (NSCLC) remain largely unknown. Somatic CNVs in BCL2L1 and MCL1 genes were tested in tumor tissues from 516 NSCLC patients in southern China; afterward, survival analyses were conducted with overall survival (OS) as outcome. Additionally, the associations between CNVs and mRNA expression levels were explored using data from 986 NSCLC patients in the Cancer Genome Atlas project. It was found that amplifications of  BCL2L1 and MCL1 were associated with unfavorable OS of NSCLC, with adjusted hazards ratio of 1.62 (95% confident interval [CI] = 1.10–2.40; P  = 0.015) and 1.39 (95% CI = 1.05–1.84; P  =   0.020), respectively. Amplifications of MCL1, but not BCL2L1, were related with higher mRNA expression levels of corresponding gene, compared with non‐amplifications ( P  = 0.005). Interestingly, after incorporating with MCL1 CNV status, clinical variables (age, sex, TNM stage, and surgical approach) showed an improved discriminatory ability to classify OS (area under curve increased from 72.2% to 74.1%; P  =   0.042, DeLong's test). Overall, MCL1 CNV might be a prognostic biomarker for NSCLC, and additional investigations are needed to validate our findings. Abstract : Copy‐number variations of MCL1 could help in the prognostic prediction of non‐small‐cell lung cancer in a Sothern Chinese population. Amplifications of MCL1 were related with higher mRNA expression levels of corresponding gene, compared with non‐amplifications.